Leveraging Digital Freight Matching Platforms, Predictive Analytics, Supply Chain Collaboration to Enhance Transportation Performance for Competitiveness SMES in Surabaya - East Java - Stephen Susanto; Agus Purnomo; Melia Eka Lestiani (Cakrawala Repositori IMWI)
The digital revolution has significantly reshaped global industries, including logistics and freight forwarding, which are vital to economic growth. In Indonesia, transportation performance plays a crucial role in logistics and contributes to the competitiveness of Micro, Small, and Medium Enterprises (SMEs). According to 2022 data from the Central Statistics Agency (BPS), East Java has approximately 1.15 million SMEs, and most logistics practitioners still depend on conventional operational methods, such as the use of physical documentation, manual workflows, and direct face-to-face interactions. This reliance is primarily due to limited awareness of the efficiency and transparency offered by digital technologies. Nevertheless, the strategic presence of logistics firms in the region has encouraged ongoing efforts to pursue technological innovation in order to strengthen competitiveness and optimize distribution system performance. This study investigates the effects of Digital Freight Matching Platforms (DFMP), Predictive Analytics (PA), and Supply Chain Collaboration (SCC) on Transportation Performance (TP) among freight forwarding companies operating in Surabaya, East Java. Using a quantitative research approach, data were collected through structured questionnaires distributed to freight forwarding practitioners and analyzed statistically to assess both the individual and combined influences of these variables. The results indicate that DFMP, PA, and SCC each exert a positive and significant influence on transportation performance. Moreover, their integration produces a synergistic effect by improving supply chain visibility, predictive accuracy, and inter-organizational coordination. These findings contribute to the empirical understanding of digital transformation in Indonesia’s logistics sector and provide policy implications for enhancing logistics innovation and competitiveness for SMEs, particularly in Surabaya, East Java.